2012
DOI: 10.3892/or.2012.1709
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological and prognostic significance of microRNA-107 and its relationship to DICER1 mRNA expression in gastric cancer

Abstract: Abstract. microRNAs (miRNAs) are small non-coding RNAs that regulate target gene expression. It is known that miRNA-107 (miR-107) promotes cancer invasion and metastasis. However, the relationship between clinicopathological factors and the prognostic significance of miR-107 for gastric cancer patients remains elusive. In this study, we evaluated the prognostic value of miR-107 using tissue samples from gastric cancer patients. Furthermore, the relationship between miR-107 and the mRNA levels of its target gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 25 publications
2
42
0
Order By: Relevance
“…23, 24 In addition, higher expression of miRNAs that target Dicer might be another critical mechanism, for example, miR103/107 were reported to target and downregulate Dicer expression and be associated with poor survival in breast cancer 15 and gastric cancer. 25 let-7 expression was inversely correlated with Dicer expression and constituted a negative feedback loop controlling Dicer expression in a panel of cancer cell lines. 16 Interestingly, miR-107 can directly interact with let-7 and reduce its expression, 26 suggesting a complex relationship between miR-107, let-7 and Dicer.…”
Section: Discussionmentioning
confidence: 99%
“…23, 24 In addition, higher expression of miRNAs that target Dicer might be another critical mechanism, for example, miR103/107 were reported to target and downregulate Dicer expression and be associated with poor survival in breast cancer 15 and gastric cancer. 25 let-7 expression was inversely correlated with Dicer expression and constituted a negative feedback loop controlling Dicer expression in a panel of cancer cell lines. 16 Interestingly, miR-107 can directly interact with let-7 and reduce its expression, 26 suggesting a complex relationship between miR-107, let-7 and Dicer.…”
Section: Discussionmentioning
confidence: 99%
“…In the Cox multivariate analysis, it was shown that miR-107 expression in GC tissues was an independent prognostic factor for OS and DFS. Their results indicate that miR-107 may be useful as an effective biomarker for prediction of a poor prognosis in GC patients [13]. However, the detailed mechanisms of miR-107 were fewly investigated in GC.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Inoue et al found that the mean expression level of miR-107 was significantly higher in the GC tissues compared to that of normal tissues. In the comparison of clinicopathological factors, miR-107 expression showed significant association with depth of tumor invasion, lymph node metastasis and tumor stage [13]. However, the detailed mechanisms of miR-107 were fewly investigated in GC.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, a circRNA-microRNA-gene regulatory network was constructed consisting of 22 circRNAs, 17 microRNAs and 130 PCGs (Fig 5, S3 Table). Among these microRNAs, several microRNAs were found related to cancers, such as has-miR-34a-5p has been reported related to several types of cancers, for example, colorectal cancer [36]; has-miR-107 exhibit aberrant expression in a variety of cancers, including hepatocellular [37], gastric cancer [38], and Glioma [39] etc. The GO analysis suggested that these PCGs mainly involved in metabolic and regulation-related process (Fig 6A).…”
Section: Resultsmentioning
confidence: 99%